Mathematics Concepts in Making Kites as a Tool in Ethno-STEM Based Learning - Risnanosanti, Risnanosanti; Ristontowi, Ristontowi; Ramadianti, Winda (International Journal of STEM Education for Sustainability, 2024)
Kite is a traditional game with many mathematical concepts, making them applicable in ethno-STEM (science, technology, engineering, and mathematics)-based learning. Therefore, this research explores the mathematical concepts inherent in kite flying related to ethnomathematics and STEM education. This research employs a qualitative exploratory approach. Data are collected through three methods: documentation, observation, and interviews. After collecting data, a descriptive analysis is conducted, including data reduction, presentation, and verification. Based on the data analysis, the mathematical concepts in kite-making include geometry, measurement, area and perimeter calculations, ratios and scales, patterns and symmetry, and arithmetic. Kite-making can be applied in ethno-STEM-based mathematics learning as it aligns with the current curriculum and adheres to STEM learning principles. Therefore, kite-making can serve as a tool for mathematics education, making learning more meaningful, enjoyable, interactive, and contextual. This research exploration suggests that numerous mathematical concepts can be further examined in ethno-STEM-based learning. Additionally, this research highlights the connection between mathematics and the socio-cultural context.